Pengaruh Kualitas Layanan Program Universal Health Coverage (UHC) Terhadap Kepuasan Pasien di Puskesmas Jagir Surabaya - Nilla, Fatma; Untarini, Nindria (Seminar Nasional Manajemen, 2025)
This study aims to determine and discuss the influence of tangibles, reliability, responsiveness, empathy, and assurance dimensions as independent variables in service quality in the Universal Health Coverage (UHC) program on patient satisfaction as the dependent variable of PBI APBD participants at the Jagir Health Center, Surabaya. The population in this study were patients of the Jagir Health Center, Surabaya. The research sample was patients of the Jagir Health Center, Surabaya who were registered as UHC PBI APBD participants totaling 127 respondents. This study used a non-probability sampling technique with a purposive sampling method. Data analysis with multiple linear regression. This study shows that empathy and assurance have a positive and significant effect on patient satisfaction. The tangibles and responsiveness dimensions have a positive and insignificant effect on patient satisfaction. The Reliability variable has a negative and insignificant effect on patient satisfaction. The practical implication of this study is that the Jagir Health Center is also expected to be able to increase effectiveness and conduct evaluations on the tangibles, reliability, and responsiveness dimensions in administrative services to increase patient satisfaction.